Validity of Norwegian Rectal Cancer Registry data at a major university hospital 1997–2005. (26th November 2015) - Sakkestad, Sunniva T.; Olsen, Bjørn C.; Karliczek, Anne; Dahl, Olav; Pfeffer, Frank
Abstract : Background. The Norwegian Rectal Cancer Registry (NRCR) has been used extensively to monitor patient treatment and outcomes since its establishment in 1993. Control of data validity is crucial to ensure reliable information, but an audit of the NRCR data validity has not been performed so far. This study aims to validate NRCR data on patients diagnosed in the period 1997–2005, Department of Surgery, Haukeland University Hospital. Material and methods. The material comprises NRCR data on all 482 patients diagnosed with rectal cancer in the period 1997–2005 at a major Norwegian university hospital. We checked 50 variables for discrepancies by comparing NRCR data with the medical records. All erroneous registrations were recorded. Results. One hundred patients (21%) had one or more data discrepancies in the registry, and 131 errors (0.5%) were noted in total. Sixteen variables (32%) had no erroneous registrations. Pre-operative CT and type of surgical procedure had the highest proportion of erroneous registrations (2.1%). Recorded errors were grouped into five variable categories: Pre-operative evaluation and adjuvant treatment (40 errors), surgical treatment (44 errors), pathological evaluation (20 errors), complications (7 errors) and oncological outcomes (20 errors). The majority of erroneous registrations (45%) were considered minor in severity, 27% were moderate and 28% were major. Conclusion. Assessment of the NRCR data from a nine-year period showed a good data validity in this hospital cohort.